2015
DOI: 10.3233/bme-151475
|View full text |Cite
|
Sign up to set email alerts
|

Sleep snoring detection using multi-layer neural networks

Abstract: Abstract. Snoring detection is important for diagnosing obstructive sleep apnea syndrome (OSAS) and other respiratory sleep disorders. In general, audio signal processing such as snoring sound analysis uses the frequency characteristics of the signal. Recently, a correlational filter Multilayer Perceptron neural network (f-MLP) has been proposed, which has the first hidden layer of correlational filter operations in frequency domain. It demonstrated a superior classification performance for the pattern sets; o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
2
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…And these algorithms have yielded promising results in characterizing the nocturnal sleep respiratory audio signal subsequently. For instance, Nguyen et al 39 and Çavuşoğlu et al 40 respectively utilized multilayer perceptron neural networks (MLP) to differentiate between snore and non-snore sounds; Arsenali et al 41 applied a long-short term memory (LSTM) model to classify snoring and non-snoring sounds after extracting MFCCs; Sun et al 42 proposed SnoreNet, a one-dimensional CNN (1D CNN) that directly operates on raw sound signals without manually crafted features; Khan et al 8 developed a two-dimension CNN (2D CNN) to analyze MFCCs images for automatically detecting snoring and applied it into a wearable gadget; Jiang et al 43 found an optional combination of Mel-spectrogram and CNN-LSTM-DNN for snoring recognition; Xie et al 44 employed a CNN to extract features from the constant-Q transformation (CQT) spectrogram, and then a recurrent neural network (RNN) was utilized to process the sequential CNN output for classifying the audio signal to snore or non-snore events. The comprehensive experiment settings and results of these researches are provided in Table 1 .…”
Section: Introductionmentioning
confidence: 99%
“…And these algorithms have yielded promising results in characterizing the nocturnal sleep respiratory audio signal subsequently. For instance, Nguyen et al 39 and Çavuşoğlu et al 40 respectively utilized multilayer perceptron neural networks (MLP) to differentiate between snore and non-snore sounds; Arsenali et al 41 applied a long-short term memory (LSTM) model to classify snoring and non-snoring sounds after extracting MFCCs; Sun et al 42 proposed SnoreNet, a one-dimensional CNN (1D CNN) that directly operates on raw sound signals without manually crafted features; Khan et al 8 developed a two-dimension CNN (2D CNN) to analyze MFCCs images for automatically detecting snoring and applied it into a wearable gadget; Jiang et al 43 found an optional combination of Mel-spectrogram and CNN-LSTM-DNN for snoring recognition; Xie et al 44 employed a CNN to extract features from the constant-Q transformation (CQT) spectrogram, and then a recurrent neural network (RNN) was utilized to process the sequential CNN output for classifying the audio signal to snore or non-snore events. The comprehensive experiment settings and results of these researches are provided in Table 1 .…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, Nguyen and Won [54] proposed a novel correlational filter ANN (f-MLP) to distinguish normal breathing patterns from snoring patterns during sleep. This ANN implements a correlational filter operation in the frequency domain in a first hidden layer aimed at improving the discriminant power of the spectral content of input patterns, followed by a second feedforward hidden layer.…”
Section: Sahs Diagnosis By Means Of Annsmentioning
confidence: 99%
“…FirasAlomariet.al [34] proposed a pattern recognition system using the energy of wavelet coefficients to categorise eight different hand gestures. In [35,36], an Artificial Neural Network (ANN) was trained using information on the level of muscular contraction and previous classifier outputs in order to determine the accuracy of the classifier's decision., YinaGuoet.al [37] used ANN to categorise six different hand movements and achieved excellent accuracy, however the system was not resilient when amputees' electrodes were shifted, changed in size, or oriented differently.…”
mentioning
confidence: 99%